Design and development of integrated chassis of three wheel prototype car using aluminum and FRP - Nur Afnan, Abdul Halim (2010)
This thesis presented about the design and development of integrated chassis of three wheel prototype car using aluminium and FRP. To improve the existing chassis design of three wheel prototype cars for Shell Eco Marathon competition, analysis of the existing chassis must be done. The analysis was carried out by using Finite Element Analysis (FEA). The parameters checked in the analysis are the displacement of the chassis structure when load applied and the weight of the chassis. Specifications of materials selection become a priority in order to construct the new chassis which can replace the ordinary design. A survey of the material used for the development of chassis design had been done in Kuantan area in order to get the most suitable material for the new chassis design. The best design was then identified based on the analysis determined from the Finite Element Analysis (FEA) technique. The specifications of the best design are the design which is light weight and has a minimum deflection of the structure when subjected on the load. The design of the final chassis design will be done by using SolidWork software which is suitable for making the 3D model of the car.